Protease-Activated Receptor-1 Contributes to Cardiac Remodeling and Hypertrophy - Pawlinski, Rafal (2007)
BACKGROUND: Protease-activated receptor-1 (PAR-1) is the high-affinity receptor for the coagulation protease thrombin. It is expressed by a variety of cell types in the heart, including cardiomyocytes and cardiac fibroblasts. We have shown that tissue factor (TF) and thrombin contribute to infarct size after cardiac ischemia-reperfusion (I/R) injury. Moreover, in vitro studies have shown that PAR-1 signaling induces hypertrophy of cardiomyocytes and proliferation of cardiac fibroblasts. The purpose of the present study was to investigate the role of PAR-1 in infarction, cardiac remodeling, and hypertrophy after I/R injury. In addition, we analyzed the effect of overexpression of PAR-1 on cardiomyocytes. METHODS AND RESULTS: We found that PAR-1 deficiency reduced dilation of the left ventricle and reduced impairment of left ventricular function 2 weeks after I/R injury. Activation of ERK1/2 was increased in injured PAR-1(−/−) mice compared with wild-type mice; however, PAR-1 deficiency did not affect infarct size. Cardiomyocyte-specific overexpression of PAR-1 in mice induced eccentric hypertrophy (increased left ventricular dimension and normal left ventricular wall thickness) and dilated cardiomyopathy. Deletion of the TF gene in cardiomyocytes reduced the eccentric hypertrophy in mice overexpressing PAR-1. CONCLUSIONS: Our results demonstrate that PAR-1 contributes to cardiac remodeling and hypertrophy. Moreover, overexpression of PAR-1 on cardiomyocytes induced eccentric hypertrophy. Inhibition of PAR-1 after myocardial infarction may represent a novel therapy to reduce hypertrophy and heart failure in humans.